Hydrogen Sulfide Mediates Tumor Cell Resistance to Thioredoxin Inhibitor - Mao, Zhimin; Yang, Xiawen; Mizutani, Sayumi; Huang, Yanru; Zhang, Zhen; Shinmori, Hideyuki; Gao, Kun; Yao, Jian (Frontiers in Oncology, 2020)
Thioredoxin (Trx) is a pro-oncogenic molecule that underlies tumor initiation, progression and chemo-resistance. PX-12, a Trx inhibitor, has been used to treat certain tumors. Currently, factors predicting tumor sensitivity to PX-12 are unclear. Given that hydrogen sulfide (H2S), a gaseous bio-mediator, promotes Trx activity, we speculated that it might affect tumor response to PX-12. Here, we tested this possibility. Exposure of several different types of tumor cells to PX-12 caused cell death, which was reversely correlated with the levels of H2S-synthesizing enzyme CSE and endogenous H2S. Inhibition of CSE sensitized tumor cells to PX-12, whereas addition of exogenous H2S elevated PX-12 resistance. Further experiments showed that H2S abolished PX-12-mediated inhibition on Trx. Mechanistic analyses revealed that H2S stimulated Trx activity. It promoted Trx from the oxidized to the reduced state. In addition, H2S directly cleaved the disulfide bond in PX-12, causing PX-12 deactivation. Additional studies found that, besides Trx, PX-12 also interacted with the thiol residues of other proteins. Intriguingly, H2S-mediated cell resistance to PX-12 could also be achieved through promotion of the thiol activity of these proteins. Addition of H2S-modified protein into culture significantly enhanced cell resistance to PX-12, whereas blockade of extracellular sulfhydryl residues sensitized cells to PX-12. Collectively, our study revealed that H2S mediated tumor cell resistance to PX-12 through multiple mechanisms involving induction of thiol activity in multiple proteins and direct inactivation of PX-12. H2S could be used to predict tumor response to PX-12 and could be targeted to enhance the therapeutic efficacy of PX-12.